2015
DOI: 10.3892/ijo.2015.3282
|View full text |Cite
|
Sign up to set email alerts
|

Activation of pancreatic stellate cells involves an EMT-like process

Abstract: Pancreatic adenocarcinoma (PDAC) and chronic pancreatitis (CP) are characterized by a desmoplastic reaction involving activated pancreatic stellate cells (PSCs). However, the mechanisms of PSC activation remain poorly understood. We examined whether the epithelial-mesenchymal transition (EMT) process might play a role in PSC activation. PSCs were isolated from a rat pancreas and characterized using immunofluorescence and immunocytochemistry. We evaluated changes in cell motility and in the expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Vlahov N et al [8] found the expression of E-cadherin lost mostly or partially in some malignant tumor deriving from epithelial tissues. The evidence showed that the E-cadherin lost or decreased in a range of tumors, such as breast cancer [3], lung cancer [9], pancreas cancer [10].…”
Section: Discussionmentioning
confidence: 99%
“…Vlahov N et al [8] found the expression of E-cadherin lost mostly or partially in some malignant tumor deriving from epithelial tissues. The evidence showed that the E-cadherin lost or decreased in a range of tumors, such as breast cancer [3], lung cancer [9], pancreas cancer [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic fibrosis is closely associated with CP and pancreatic cancer (PC) and it induces severe damage in the pancreas. CP and PC are characterized by a desmoplastic reaction that involves activated pancreatic stellate cells (PSCs) (1)(2)(3). This reaction promotes the growth and invasion of tumor cells (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…CP and PC are characterized by a desmoplastic reaction that involves activated pancreatic stellate cells (PSCs) (1)(2)(3). This reaction promotes the growth and invasion of tumor cells (3)(4)(5). The activation of PSCs has been previously proposed as the key initiating step in pancreatic fibrosis (6) and a major source of extracellular matrix (ECM) deposition during pancreatic injury (7).…”
Section: Introductionmentioning
confidence: 99%
“…A special characteristic property of the EMT pathway is the transition of epithelial E‐cadherin to mesenchymal N‐cadherin. PSCs in PC can promote the EMT pathway by reducing E‐cadherin expression and elevating vimentin and Snail1 expressions . Due to the lack of specific evidence and limited information regarding the specific mechanisms involved, it has been assumed that aberrant vascularity and augmented fibrosis due to PSC activation results in hypoxia, which can promote EMT transition in PC.…”
Section: Introductionmentioning
confidence: 99%
“…PSCs in PC can promote the EMT pathway by reducing E-cadherin expression and elevating vimentin and Snail1 expressions. [9][10][11] Due to the lack of specific evidence and limited information regarding the specific mechanisms involved, it has been assumed that aberrant vascularity and augmented fibrosis due to PSC activation results in hypoxia, which can promote EMT transition in PC. It has previously been demonstrated that activation of PSCs, increasing EMT and DNA methylation could be a potential therapeutic strategy in the treatment of PC.…”
Section: Introductionmentioning
confidence: 99%